EFEKTIVITAS PENYULUHAN KEHUTANAN DALAM MENDUKUNG KEGIATAN KONSERVASI TANAH DAN AIR DI SUB DAERAH ALIRAN SUNGAI KEDUANG KABUPATEN WONOGIRI - , Agung Praptadi, Dr. Agr. Sri Peni Wastutiningsih ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Erosion which happens in Keduang Sub-watershed has resulted sedimentation intensively of Gajah Mungkur Dam. It can disrupt function of the dam as flood control, irrigation, power generation, tourism, and fisheries. Hypothesis of this condition is as results of land use catchment area that do not following of rules soil and water conservation. In addition, level of people behavior is assumed as follows: low levels of knowledge, attitudes, and skills in terms of soil and water conservation caused by lack of effectiveness forestry extension. This study aims to: 1) analyze contribution extention effectiveness factors of 3 dimensions: goal achievement of extension, sustainability of extension, and farmer satisfaction